ChemInform Abstract: Three‐Component and One‐Pot Reaction Between Phenacyl Bromide and Primary Amines in the Presence of Carbon Disulfide. Issue 29 (1st July 2013) - Hassanabadi, Alireza; Khandan‐Barani, Khatereh
Abstract: The main features of the reported methodology are neutral reaction conditions and starting materials which need not to be mixed with any activation nor modification.